(untitled) (International journal of artificial intelligence, 2025)
This article explores digital technology neologisms in the English and Uzbek languages with a focus on their lexical-semantic features and translation challenges. The rapid development of information and communication technologies has led to the emergence of numerous new terms that reflect technological innovations, digital practices, and online communication. The study aims to identify the main semantic groups of digital neologisms, analyze their word-formation mechanisms, and examine the strategies used to translate them between English and Uzbek. A comparative and descriptive methodology is employed, incorporating lexical-semantic analysis, contextual interpretation, and translation analysis. The findings reveal that English digital neologisms are predominantly formed through compounding, blending, and abbreviation, while Uzbek equivalents often rely on borrowing, calquing, and semantic adaptation. The research also highlights cases of semantic shift and partial equivalence that arise in the translation process. The results contribute to a deeper understanding of digital terminology development and provide practical implications for translators, lexicographers, and language educators working in the field of digital communication.